Prinsip-prinsip Komunikasi dalam Al-Qurâan - Bahrudin, Bahrudin (Jurnal Ilmu Dakwah, 2010)
Doing communicate constitute something needed by almost each human activity. By communicate, human can interact one and other; to present his purpose and objectÂ  and to express attitude and feeling contens that created one related human between. How everÂ  it is not any kindÂ  can be apllied but only communicate based by the strong etic that having ability toÂ  productÂ Â  a society relation patternÂ  characterized e.g.: harmony, warm, attractive, to respect one another, not to discriminate and not to force the desire and his self opinion to other. This pattern have relate to the holy Qurâan with term such: qaulan balighan, qaulan maisuran, qaulan kariÂman, qaulan maârufan, qaulan layyinan, qaulan sadidan,and so on that verificated and examinated in Islamic socius living.